A gene expression map of host immune response in human brucellosis - Mitroulis, Ioannis; Chrysanthopoulou, Akrivi; Divolis, Georgios; Ioannidis, Charalampos; Ntinopoulou, Maria; Tasis, Athanasios; Konstantinidis, Theocharis; Antoniadou, Christina; Soteriou, Natalia; Lallas, George; Mitka, Stella; Lesche, Mathias; et al. (Frontiers in Immunology, 2022)
Brucellosis is a common zoonotic disease caused by intracellular pathogens of the genus Brucella. Brucella infects macrophages and evades clearance mechanisms, thus resulting in chronic parasitism. Herein, we studied the molecular changes that take place in human brucellosis both in vitro and ex vivo. RNA sequencing was performed in primary human macrophages (Μφ) and polymorphonuclear neutrophils (PMNs) infected with a clinical strain of Brucella spp. We observed a downregulation in the expression of genes involved in host response, such as TNF signaling, IL-1β production, and phagosome formation in Μφ, and phosphatidylinositol signaling and TNF signaling in PMNs, being in line with the ability of the pathogen to survive within phagocytes. Further transcriptomic analysis of isolated peripheral blood mononuclear cells (PBMCs) and PMNs from patients with acute brucellosis before treatment initiation and after successful treatment revealed a positive correlation of the molecular signature of active disease with pathways associated with response to interferons (IFN). We identified 24 common genes that were significantly altered in both PMNs and PBMCs, including genes involved in IFN signaling that were downregulated after treatment in both cell populations, and IL1R1 that was upregulated. The concentration of several inflammatory mediators was measured in the serum of these patients, and levels of IFN-γ, IL-1β and IL-6 were found significantly increased before the treatment of acute brucellosis. An independent cohort of patients with chronic brucellosis also revealed increased levels of IFN-γ during relapse compared to remissions. Taken together, this study provides for the first time an in-depth analysis of the transcriptomic alterations that take place in human phagocytes upon infection, and in peripheral blood immune populations during active disease.